Mapeamento de risco de incêndios florestais em parques, a partir de análise multicritério - Souza, Nicollas Gabriel Assunção e (2022)
The Parque Estadual do Pau Furado is a Conservation Unit created with the purpose of ensuring the preservation of animal and plant species present in the mesoregion of Triângulo Mineiro and Alto Paranaíba. The park, mostly represented by the Cerrado biome, suffers from fire occurrences mainly during the dry season. Aiming at identifying the most susceptible areas to forest fires, this work used multicriteria analysis applied to geospatial information for the elaboration of an integrated fire risk map in the park. In order to develop this map, the fire influence variable must be taken into account, the variables investigated in this research were: land use and occupation, distance from roads and urban area, slope, slope orientation, hypsometry, and precipitation over a period of five years in the studied area. In order to understand how each of these variables can interfere with fires, the thematic map must be prepared and, later, the susceptibility map, for each variable. From the integration of these susceptibility maps, the integrated forest fire risk map is generated, using the weighted average between the variables. Therefore, the application of the analytic hierarchy process is essential for the distribution of weights for each variable. From the generated maps, it was possible to verify that 6.18% of the park area presents a very high risk for the occurrence of fires, in addition, the southern region of the park showed greater vulnerability to fire, which is confirmed by the map of fire focus. We can say that the methodology used in this research can be useful to managers of this, and other parks, as material to assist in decision-making for preventive measures against forest fires.